Dogs with macroadenomas have lower body temperature and heart rate than dogs with microadenomas. (September 2017) - Benchekroun, Ghita; Desquilbet, Loic; Herrtage, Michael E.; Jeffery, Nick D.; Rosenberg, Dan; Granger, Nicolas
Highlights: Cut-off values of 38.3 °C and 84 bpm allowed discrimination between pituitary macroadenomas and microadenomas. Fifty nine percent of dogs with pituitary macroadenomas had a body temperature ≤ 38.3 °C. Forty one percent of dogs with pituitary macroadenomas had a heart rate ≤ 84 bpm. Seventy five percent of Cushing dogs with vague neurological signs had a heart rate ≤ 84 bpm or a body temperature ≤ 38.3 °C. Abstract: Pituitary macroadenomas compress the hypothalamus, which partly regulates heart rate and body temperature. The aim of this study was to investigate whether heart rate and/or body temperature could aid in clinically differentiating dogs with macroadenomas from dogs with microadenomas (i.e. small non-compressive pituitary mass). Two groups of dogs diagnosed with pituitary-dependent hyperadrenocorticism (i.e. Cushing's disease) were included. Heart rate and body temperature were collected on initial presentation before any procedure. Dogs with macroadenoma had a significantly lower heart rate and body temperature ( P <  0.01) compared to dogs with microadenoma. We suggest that the combined cut-off values of 84 beats per minutes and 38.3 °C in dogs with Cushing's disease, especially with vague neurological signs (nine of 12 dogs = 75%), might help to suspect the presence of a macroadenoma.